Clinical validation of a machine‐learning‐based handheld 3‐dimensional infrared wound imaging device in venous leg ulcers. Issue 2 (14th June 2021) - Chan, Kai Siang; Liang, Shanying; Cho, Yuan Teng; Chan, Yam Meng; Tan, Audrey Hui Min; Muthuveerappa, Sivakami; Lai, Tina Peiting; Goh, Cheng Cheng; Joseph, Annie; Hong, Qiantai; Yong, Enming; Zhang, Li; et al.
Abstract: Chronic venous insufficiency is a chronic disease of the venous system with a prevalence of 25% to 40% in females and 10% to 20% in males. Venous leg ulcers (VLUs) result from venous insufficiency. VLUs have a prevalence of 0.18% to 1% with a 1‐year recurrence of 25% to 50%, bearing significant socioeconomic burden. It is therefore important for regular assessment and monitoring of VLUs to prevent worsening. Our study aims to assess the intra‐ and inter‐rater reliability of a machine learning‐based handheld 3‐dimensional infrared wound imaging device (WoundAide [WA] imaging system, Konica Minolta Inc, Tokyo, Japan) compared with traditional measurements by trained wound nurse. This is a prospective cross‐sectional study on 52 patients with VLUs from September 2019 to January 2021 using three WA imaging systems. Baseline patient profile and clinical demographics were collected. Basic wound parameters (length, width and area) were collected for both traditional measurements and measurements taken by the WA imaging systems. Intra‐ and inter‐rater reliability was analysed using intra‐class correlation statistics. A total of 222 wound images from 52 patients were assessed. There is excellent intra‐rater reliability of the WA imaging system on three different image captures of the same wound (intra‐rater reliability ranging 0.978‐0.992). In addition, there is excellent inter‐rater reliability between the three WA imaging systems for length (0.987), width (0.990) and area (0.995). Good inter‐rater reliability for length and width (range 0.875‐0.900) and excellent inter‐rater reliability (range 0.932‐0.950) were obtained between wound nurse measurement and each of the WA imaging system. In conclusion, high intra‐ and inter‐rater reliability was obtained for the WA imaging systems. We also obtained high inter‐rater reliability of WA measurements against traditional wound measurement. The WA imaging system is a useful clinical adjunct in the monitoring of VLU wound documentation.